دراسة تصنيفية لأنواع فوق عائلة Arietelloidea من رتبة (Calanoida) في المياه البحرية الساحلية لمدينة اللاذقية (Latakia University Journal -Basic Sciences Series, 2018)
This study was performed on the superfamily Arietelloidea (order Calanoida) which forms a major part in marine food chains of fish. The present study is the first in the Syrian marine coastal water and is considered a contribution to the study of the Syrian marine biodiversity. The samples were collected from 7 stations by vertical haul. We defined 9 species belonging to 4 genera and 4 families, These species are : Euaugabtilus hecticus (Giesbrecht), Lucicutia flavicornis (Claus), L. gimina Farran, L. ovalis (Gisbrecht), Pleuromamma gracilis (Claus), P. abdominalis (Lubbock), L. longicornis (Giesbrecht), L. curta Farran & Heterorabdus papilliger (Claus). The last three species are new in Syria ; but the last one was recorded in Lebanon. أجريت دراسة تصنيفية لأنواع فوق عائلة Arietelloidea من رتبة Calanoida  التي تشكل حلقة أساسية في السلسلة الغذائية للأسماك ويعد هذا البحث الأول من نوعه في المياه البحرية الساحلية ، وهو مساهمة في دراسة التنوع الحيوي البحري السوري. تم الإعتيان بطريقة الجمع العمودي للمياه البحرية الساحلية لمدينة اللاذقية من سبع محطات مختلفة. تم تحديد 9 أنواع تنتمي إلى 4 أجناس و4 عائلات وهي : Euaugabtilus hecticus (Giesbrecht), Lucicutia flavicornis (Claus), L. gimina Farran, L. ovalis (Gisbrecht), Pleuromamma gracilis (Claus), P. abdominalis (Lubbock), L. longicornis (Giesbrecht), L. curta Farran  & Heterorabdus papilliger (Claus).   و تسجل الأنواع الثلاثة الأخيرة لأول مرة في سورية ولكن النوع الأخير سجل لأول مرة في المياه البحرية اللبنانية.